2021
DOI: 10.1002/gepi.22382
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating European GWAS findings improve polygenic risk prediction accuracy of breast cancer among East Asians

Abstract: Previous genome‐wide association studies (GWASs) have been largely focused on European (EUR) populations. However, polygenic risk scores (PRSs) derived from EUR have been shown to perform worse in non‐EURs compared with EURs. In this study, we aim to improve PRS prediction in East Asians (EASs). We introduce a rescaled meta‐analysis framework to combine both EUR (N = 122,175) and EAS (N = 30,801) GWAS summary statistics. To improve PRS prediction in EASs, we use a scaling factor to up‐weight the EAS data, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…We previously demonstrated that linearly combining PRS from European and non-European training samples improves cross-population prediction accuracy 7 . However, these previous results did not incorporate causal effects and used P+T, which is highly inaccurate despite its widespread use 11,[13][14][15][16][17][18]23,31,[52][53][54][55][56] , as PolyPred obtained up to 164% greater accuracy than P+T. In conclusion, PolyPred and its summary statistic-based analogues substantially improve cross-population polygenic prediction accuracy, ameliorating health disparities 13 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We previously demonstrated that linearly combining PRS from European and non-European training samples improves cross-population prediction accuracy 7 . However, these previous results did not incorporate causal effects and used P+T, which is highly inaccurate despite its widespread use 11,[13][14][15][16][17][18]23,31,[52][53][54][55][56] , as PolyPred obtained up to 164% greater accuracy than P+T. In conclusion, PolyPred and its summary statistic-based analogues substantially improve cross-population polygenic prediction accuracy, ameliorating health disparities 13 .…”
Section: Discussionmentioning
confidence: 91%
“…Among the published methods, BOLT-LMM attained the highest prediction accuracy in all target populations (differences between BOLT-LMM and SBayesR were small and not statistically significant, but the difference between BOLT-LMM and PRS-CS was statistically significant in non-British Europeans); as noted above, the higher accuracy of BOLT-LMM vs. SBayesR and PRS-CS does not imply that BOLT-LMM is a superior method, as BOLT-LMM analyzes individual-level training data whereas SBayesR and PRS-CS analyze summary statistics. P+T was much less accurate than the other methods (despite its widespread recent use 11,[13][14][15][16][17][18]23,31,[52][53][54][55][56] ), suffering relative losses of 37-50% vs. BOLT-LMM. We thus used BOLT-LMM as a benchmark, conservatively assessing the statistical significance of improvements vs. BOLT-LMM via genomic block-jackknife across 200 genomic regions (Methods).…”
Section: Analysis Of 4 Uk Biobank Populations Using Uk Biobank British Training Datamentioning
confidence: 93%
See 2 more Smart Citations
“…Polygenic risk scores (PRS) can identify individuals at elevated risk of complex diseases, providing opportunities for preventative action [1][2][3][4][5][6] . However, many studies have shown that PRS based on European training data attain lower accuracy when applied to populations of non-European ancestry [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . This loss of accuracy is primarily driven by LD differences [12][13][14][15] , allele frequency differences (including populationspecific SNPs) 13,14,27 , and causal effect size differences [12][13][14][28][29][30][31] , though differences in heritability also play a minor role 13,14,32 .…”
Section: Introductionmentioning
confidence: 99%